The role of platelet-derived growth factor receptor in eotaxin signaling of eosinophils. - Adachi, T; Hanaka, S; Yano, T; Yamamura, K; Yoshihara, H; Nagase, H; Chihara, J; Ohta, K (2006)
BACKGROUND: Receptor tyrosine kinases (RTKs) such as epidermal growth factor receptor (EGFR) and platelet-derived growth factor receptor (PDGFR) are capable of eliciting kinase activity after ligand binding. In several cells, RTKs are activated via the G-protein-coupled receptor independent of the ligand-RTK interaction. We have previously found that EGFR is transactivated via CC chemokine receptor 3 in bronchial epithelial cells and that this pathway is important for mitogen-activated protein (MAP) kinase activation and cytokine production. It has recently been suggested that hypereosinophilic syndrome results from the fusion tyrosine kinase FIP1L1-PDGFRA. Although it is possible that the PDGFR signal is involved in eosinophil function, the details are still unclear. METHODS: Blood eosinophils were purified using Percoll and anti-CD16 antibody-coated magnetic beads. Expression of PDGFR mRNA was examined by RT-PCR. After stimulating eosinophils with eotaxin, the phosphorylation of MAP kinases was examined by Western blotting with the antiphosphospecific MAP kinase antibody. The eotaxin-induced eosinophil chemotaxis was studied using Boyden chambers. RESULTS: Eosinophils expressed PDGFRbeta mRNA in 4 out of 8 donors, while PDGFRalpha mRNA was expressed in only 1 donor. Protein expression of PDGFR was also detectable in eosinophils from some donors. AG1295, a specific inhibitor of PDGFR, showed dose-dependent inhibition of eotaxin-induced MAP kinase phosphorylation in the eosinophils expressing PDGFRbeta mRNA. The chemotaxis of these eosinophils was significantly inhibited by AG1295 (n = 3). CONCLUSIONS: Our results suggest that PDGFR modifies the CCR3-MAP kinase signaling pathway and chemotactic response in some donors. The pharmacological targeting of PDGFR may be a new strategy to treat eosinophilic disorders.